SWEAR WORDS BY ANDERSSON THEORY IN THE MOVIE WHIPLASH - Venny Christie Sembiring; Iskandar Rosyidin; Cita Hikmah Yanti (Universitas Sarjanawiyata Tamansiswa, 2019)
This study discusses about the usage of swear words by the characters in the movie Whiplash. The aim of this study is to classify the types of swear words and to analyze the motives which cause the characters use the swear words by using Andersson’s theory. In this study, descriptive method is employed to analyze all the swear words which found in the movie. To analyze the data, the researcher watches the movie for several times. Second, find for theory that supports this research from the books and internet. Third, search and download the script from the internet. Fourth, Identifying all the swear words and last, grouping all the data, classifying them according to types and motives by using Andersson’s theory. The finding of this study show that Auxiliary swear word is the dominant type and Linguistics motives is the dominant motives that influencing the characters to using swear words.